Challenges in operationalizing the water–energy–food nexus. Issue 11 (18th August 2017) - Liu, J.; Yang, H.; Cudennec, C.; Gain, A.K.; Hoff, H.; Lawford, R.; Qi, J.; Strasser, L. de; Yillia, P.T.; Zheng, C.
ABSTRACT: Concerns about the water–energy–food (WEF) nexus have motivated many discussions regarding new approaches for managing water, energy and food resources. Despite the progress in recent years, there remain many challenges in scientific research on the WEF nexus, while implementation as a management tool is just beginning. The scientific challenges are primarily related to data, information and knowledge gaps in our understanding of the WEF inter-linkages. Our ability to untangle the WEF nexus is also limited by the lack of systematic tools that could address all the trade-offs involved in the nexus. Future research needs to strengthen the pool of information. It is also important to develop integrated software platforms and tools for systematic analysis of the WEF nexus. The experience made in integrated water resources management in the hydrological community, especially in the framework of Panta Rhei, is particularly well suited to take a lead in these advances.